LEGAL ANALYSIS OF GOLD PAWN AGREEMENT IN SYARIAH BANK (Study at PT. Bank Syariah Indonesia Kutacane Branch Office) - Azhari, Ayu (Inspiring Law Journal, 2025)
Islamic banking in Indonesia is rapidly growing, especially with gold pawn services offered by Bank Syariah Indonesia (BSI). This product is popular for its quick process and compliance with Sharia principles. However, gold pawn agreements at BSI face legal challenges regarding adherence to Sharia and national regulations. This study analyzes the characteristics, implementation, and legal implications of these agreements using an empirical legal method with a juridical-sociological approach based on literature review and interviews at BSI KC Kutacane. Findings show that BSI’s gold pawning uses Sharia contracts, is free of usury, and supervised by OJK and Fatwa DSN-MUI. The process begins with customer application and asset evaluation, but the ujrah fee calculation does not align with fatwa, as it is based on the loan amount rather than actual costs. If customers fail to redeem, the goods are auctioned and remaining debts remain their responsibility